'I can spot them a mile off': Community shopkeepers' experience of alcohol test-purchasing. (June 2014) - Forsyth, Alasdair J. M.; Davidson, Neil; Ellaway, Anne
<x xml:space="preserve">Abstract</x> Aims: Test-purchasing (using volunteers to attempt an apparent under-age purchase) can be used as an enforcement intervention against retailers who sell alcohol to minors. This article will investigate whether community shopkeepers, familiar with alcohol test-purchasing protocols, are able to distinguish volunteers from genuine under-age customers. Methods: Thirty-six qualitative interviews were conducted with community shopkeepers, the retailers most often associated with under-age sales, working in convenience stores located in socially-contrasting areas of Glasgow, Scotland, 24 of which were licensed to sell alcohol. Findings: Interviewees provided details of the strategies they used to prevent under-age sales. Robust age-verification, set 7.5 above legal-age of purchase, was felt to be particularly effective. Although, they were apprehensive of test-purchases, experienced retailers reported that they always knew when one was taking place in their shop, because volunteers were not sourced locally and, in contrast to real under-age customers, they were honest and compliant. Conclusions: Although making retailers more aware of their responsibilities, increased familiarity with the protocols of test-purchasing can allow vendors to be certain who real under-age customers are, potentially making low-risk sales to minors possible. Test-purchasing protocols (e.g. volunteers ages) should be re-oriented to keep pace with more robust age-verification checks.